Determinasi Kinerja Kesehatan Nasional di Negara ASEAN: Analisis Panel 2000-2023 Berdasarkan Tingkat Pengangguran, Belanja Pemerintah Sektor Kesehatan, dan Urbanisasi - Muhamad Lucky Souma; Dini Khaerina Azahra; Rifa Naila Rizki; Daffa Shafwan Aksan; Melva Firdhian Nabillah; Fitri Amalia (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study examines the determinants of national health performance in 10 ASEAN countries from 2000 to 2023 using panel data regression. Life expectancy serves as the primary indicator of health outcomes, while the independent variables include unemployment, government health expenditure, urbanization, and GDP per capita. Model specification tests indicate that the Fixed Effects model is more consistent; however, the presence of heteroskedasticity makes the Feasible Generalized Least Squares (FGLS) approach more appropriate for interpretation. The findings show that unemployment has a significant negative effect on life expectancy, whereas government health expenditure, urbanization, and GDP per capita have significant positive effects. These results highlight the importance of macroeconomic conditions, public spending capacity, and demographic dynamics in shaping health outcomes across ASEAN countries. The study provides empirical evidence that strengthening labor markets, increasing investment in the health sector, and managing urbanization effectively are essential to improving health performance and reducing disparities within the region.